2022
DOI: 10.1111/cfs.12955
|View full text |Cite
|
Sign up to set email alerts
|

Working and caring for a disabled adopted child during a pandemic

Abstract: Integrating work and family demands can be challenging for families caring for a child with one or more disabilities. The pandemic and its changes to work, schooling and service delivery potentially added to these challenges. This exploratory mixed methods study sought to understand how the pandemic affected adoptive parents' work-life fit and service use. A total of 200 participants responded to survey questions about parenting an adopted child with a disability prior to, and after, the onset of Covid-19. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Parents, especially parents of children with disabilities, reported higher levels of stress, mental health symptoms, burnout, and social isolation worldwide (Asbury et al, 2021;Hong et al, 2021;Kerr et al, 2021;Lee et al, 2021;Lipkin & Crepeau-Hobson, 2023;Manning et al, 2021;Sellmaier & Kim, 2022;Willner et al, 2020). In Willner et al's (2020) study, parents of children with intellectual disabilities living in the UK showed significantly greater levels of anxiety, depression, defeat/entrapment, and wish-fulfillment coping styles and received significantly less social support than parents of children without disabilities.…”
Section: A Snapshot Of the Impact Of Covid-19 On Parents Of Students ...mentioning
confidence: 94%
See 3 more Smart Citations
“…Parents, especially parents of children with disabilities, reported higher levels of stress, mental health symptoms, burnout, and social isolation worldwide (Asbury et al, 2021;Hong et al, 2021;Kerr et al, 2021;Lee et al, 2021;Lipkin & Crepeau-Hobson, 2023;Manning et al, 2021;Sellmaier & Kim, 2022;Willner et al, 2020). In Willner et al's (2020) study, parents of children with intellectual disabilities living in the UK showed significantly greater levels of anxiety, depression, defeat/entrapment, and wish-fulfillment coping styles and received significantly less social support than parents of children without disabilities.…”
Section: A Snapshot Of the Impact Of Covid-19 On Parents Of Students ...mentioning
confidence: 94%
“…Therefore, many women abandoned their jobs or significantly reduced work time for childcare and remote schooling responsibilities (Collins et al, 2020). Moreover, parents, especially from underserved backgrounds, had various barriers, such as limited space at home, access to the internet, and knowledge of digital literacy, in providing educational support to their children (Averett, 2021;Özer et al, 2020;Schuck & Lambert, 2020;Sellmaier & Kim, 2022). Special education professionals described that many parents had to step in as teachers, taking on new responsibilities that ranged from logging into classes to even developing lesson plans (Long et al, 2021;Schuck & Lambert, 2020).…”
Section: A Snapshot Of the Impact Of Covid-19 On Parents Of Students ...mentioning
confidence: 99%
See 2 more Smart Citations